Sak̕art̕velos istoria saxelmjġvanelo sašualo skolis up̕rosi klasebisat̕vis : moconeebulia Sak̕. SSR Ministrt̕a sabčos mier - Berjenišvili, Niko 1895-1965; J̌avaxišvili, Ivane 1876-1940; J̌anašia, Simon 1900-1947 (Sak̕art̕velos SSR Saxelmcip̕o gamomc̕emloba, 2016)
This publication is a republication of a title that was published several times from 1943-1956. It is not strictly a reprint as some material has been added that had been previously taken out by the censors